2017
DOI: 10.1016/j.jconhyd.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the evolution and migration of a methane gas plume in an unconfined sandy aquifer using time-lapse GPR and ERT

Abstract: Fugitive methane (CH) leakage associated with conventional and unconventional petroleum development (e.g., shale gas) may pose significant risks to shallow groundwater. While the potential threat of stray (CH) gas in aquifers has been acknowledged, few studies have examined the nature of its migration and fate in a shallow groundwater flow system. This study examines the geophysical responses observed from surface during a 72day field-scale simulated CH leak in an unconfined sandy aquifer at Canadian Forces Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 46 publications
4
60
0
Order By: Relevance
“…In this scenario, previously identified during the investigation of the Ross Department store explosion in 1985 (Jenden, ; Schoell et al, ), methane could migrate from deep oil pools along leaking oil well casings or up faults to the shallower groundwater. Recent studies have investigated the effects of the supersaturation of methane in groundwater resulting in a free gas phase migration (Cahill et al, ; Steelman et al, ). However, the theoretical solubility limits for LAB deep wells (at 30°C and 50 bar) would be ~903 mg/L methane, which is much greater than the highest concentration observed (LA‐19; 150 mg/L methane, 488 mbls; Tables and ), indicating that methane is not supersaturated in the aquifers, and dissolved gas phase transport is predominant.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, previously identified during the investigation of the Ross Department store explosion in 1985 (Jenden, ; Schoell et al, ), methane could migrate from deep oil pools along leaking oil well casings or up faults to the shallower groundwater. Recent studies have investigated the effects of the supersaturation of methane in groundwater resulting in a free gas phase migration (Cahill et al, ; Steelman et al, ). However, the theoretical solubility limits for LAB deep wells (at 30°C and 50 bar) would be ~903 mg/L methane, which is much greater than the highest concentration observed (LA‐19; 150 mg/L methane, 488 mbls; Tables and ), indicating that methane is not supersaturated in the aquifers, and dissolved gas phase transport is predominant.…”
Section: Discussionmentioning
confidence: 99%
“…54 It was shown that, after entering the aquifer, free-phase methane preferentially migrated upward due to buoyancy while a significant portion migrated laterally five times faster than advective groundwater flow, due to subtle grain-scale bedding. 55 Results also showed that during the experimental leakage event, dewatered gas-migration channels formed and acted to facilitate emissions to the atmosphere 26 and limit retention in groundwater. After gas injection was stopped, these channels collapsed resulting in increased gas-water mixing, increased levels of dissolved hydrocarbon gases in groundwater, 56 and cessation of emissions to the atmosphere.…”
Section: Migration Impacts and Fate Of Fugitive Gasmentioning
confidence: 91%
“…To circumvent such research challenges, a multidisciplinary controlled natural‐gas release investigation was recently completed, offering an opportunity to advance understanding of subsurface gas migration from a point source in a shallow groundwater system . It was shown that, after entering the aquifer, free‐phase methane preferentially migrated upward due to buoyancy while a significant portion migrated laterally five times faster than advective groundwater flow, due to subtle grain‐scale bedding . Results also showed that during the experimental leakage event, dewatered gas‐migration channels formed and acted to facilitate emissions to the atmosphere and limit retention in groundwater.…”
Section: Key Knowledge Gaps Relating To Gas Migration and Fugitive Gasmentioning
confidence: 99%
“…Methane injected into the shallow aquifer at Borden resulted in unexpected, strong lateral movement of free gas, along with a dissolved methane plume and dispersion in the direction of gas flow. Hydrochemical impacts persisted for over a year (Steelman et al ). These types of measurements must be done at many locations and under many different hydrogeologic conditions before a common pattern might emerge.…”
Section: Science Needsmentioning
confidence: 99%